Kinetic processes in Te-Se glasses - Svoboda, Roman; Honcová, Pavla; Málek, Jiří (University of Pardubice, 2011)
Structural relaxation kinetics and crystallization kinetics of chosen compositions from the Se-Te glassy system were studied under non-isothermal conditions by using differential scanning calorimetry in dependence on particle size. The purpose of this contribution is to demonstrate the extent of information accessible by the present-day kinetic analysis provided by the differential scanning calorimetry and to suggest its importance and merit for the development of new high-tech PCM materials. Enthalpic relaxation was described on the basis of Tool–Narayanaswamy–Moynihan model. Single set of TNM parameters was obtained from the curve-fitting procedure for each studied glass. A comparison with our previous measurements on a-Se was made and the development of particular TNM parameters with increasing Te content was discussed in terms of changes in molecular structure of the material. The curve-fitting results were further verified by several independent non-fitting methods. The crystallization kinetics was described in terms of the nucleation-growth Johnson–Mehl–Avrami model. Complexity of the crystallization process was in this case represented by very closely overlapping consecutive competing surface and bulk nucleation-growth mechanisms. Mutual interactions of both mechanisms as well as all other observed effects were explained in terms of thermal gradients, surface crystallization centres arising from the sample preparation treatments and changing amount of volume nuclei originating from the combination of prenucleation period and the very glass preparation phase. Advanced error analysis was performed for each step of the kinetic study. A new criterion for quick determination of the dominating crystallization mechanism — surface or bulk — was introduced.